Deconstructing Cultural Myths: Films of Alain Resnais and Oshima Nagisa - Chen, Simon (Tufts University. Tisch Library., 2020)
This research delves into the formation and deconstruction of the notion "cultural myth" in national rhetorics of France and Japan in the 60s. By comparing films of Alain Resnais and Nagisa Oshima, the essay, with regard to their different cultural contexts, will examine how the two filmmakers utilize innovative filmmaking techniques such as tracking shots and film-within-film to challenge state-sponsored myth of national unity and aesthetic tradition.; Submitted in partial fulfillment of the grant requirement of the Tufts Summer Scholars Program.